Penerapan Bimbingan Kelompok Berbasis Lalaran untuk Mengatasi Kecemasan terhadap Hafalan Santri Di Pondok Pesantren - Fadliyah, Jamilatul; Hernisawati, Hernisawati (Bulletin of Counseling and Psychotherapy, 2020)
Basically everyone has felt anxiety at a certain moment in his life. But if the anxiety experienced is very excessive and left alone without the direction of someone can be very detrimental to the individual. As for memorization, anxiety often arises experienced by students. The need for guidance to facilitate students in memorizing and can reduce the level of anxiety they experience. Therefore, the formation of the application of group-based guidance in order to reduce anxiety in memorizing students in boarding schools. From the results of the normality test results Sig. obtained a probability value> 0.05 then the results can be stated normally. From the test results Sig. Based on the Mean of Sig. 0.058> 0.05 variance of the data resulting from the application of group-based guidance in the experimental class and the control class is homogeneous. Based on the results of the group statistics above we can find out from the data generated by the experimental class as many as 10 people have an average value of 152.70 and in the control class as many as 10 people have an average value of 124.00 that has been obtained by each class. Independent samples test output table test results of students learning we can know the value of Sig. (2-tailed) is 0,000. Based on the criteria in decision making 0,000 <0.05, then Ho is rejected and Ha is accepted. So that there is a significant influence in the application of group-based guidance in overcoming anxiety over memorization of the Sabrowi C class of Roudlotut Tholibin Islamic Boarding School.